2006
DOI: 10.7863/jum.2006.25.10.1291
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Measurement of Achilles Tendons in Asymptomatic Subjects

Abstract: Sonography is a useful imaging tool in the evaluation of Achilles tendons. Normal variations of the tendon morphologic characteristics should be considered in the clinical diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 30 publications
6
81
2
Order By: Relevance
“…Egwu et al [23] measured the left Achilles tendon thickness was greater than the right side. Pang and Ying [17] observed that the length of Achilles tendon differed between the dominant and non-dominant side. Balius et al [24] found the same results on cadavers.…”
Section: Anatomy • Volume 9 / Issue 3 / December 2015mentioning
confidence: 99%
See 1 more Smart Citation
“…Egwu et al [23] measured the left Achilles tendon thickness was greater than the right side. Pang and Ying [17] observed that the length of Achilles tendon differed between the dominant and non-dominant side. Balius et al [24] found the same results on cadavers.…”
Section: Anatomy • Volume 9 / Issue 3 / December 2015mentioning
confidence: 99%
“…[2] Our findings for Achilles tendon thickness are around 4 mm. Van Schie et al [14] measured Achilles tendon thickness as 6.8±1.2 mm, Fahlstrom and Alfredson [15] measuring 6±1 mm, Mabuchi et al [16] 6.03±0.2 mm, Pang and Ying [17] 5.1±0.6 mm, and Kallinen and Suomin [18] 5.7±1.4 mm. There are differences in Achilles tendon sizes between males and females, possibly due to differences in muscle strength and mechanical properties.…”
Section: Anatomy • Volume 9 / Issue 3 / December 2015mentioning
confidence: 99%
“…Mabuchi et al [13] United States of America 6.03±0.2 mm Pang and Yin [14] Hong Kong 5.1±0.6 mm Kallinen and Suomin [15] Finland 5.7±1.4 mm Ricardo et al [16] Brazil 5.5±0.6 mm @ C I C E d i z i o n i I n t e r n a z i o n a l i ed 7 . Morphometric study involving transverse and antero-posterior diameter of TC done using ultrasound technique in Brazilian population reported no significant differences between left and right side tendons.…”
Section: Study Done By Study Population Thickness Of Tcmentioning
confidence: 99%
“…They de ter mi ned that pre fe ren ce had no ef fect on Ac hilles ten don thick ness and per for man ce. 28 Holmes et al analy zed the iso ki ne tic strengths of qu ad ri ceps musc le and hams tring gro up musc les in high school stu dents. They de ter mi ned no dif fe ren ce bet ween pre fer red and non-pre fer red si des in ma les or fe ma les.…”
Section: Discussionmentioning
confidence: 99%